Ambient Intelligence- Software and Applications - 7th International Symposium on Ambient Intelligence (ISAmI 2016) - Lindgren, Helena; De Paz, Juan F.; Novais, Paulo; Fernández-Caballero, Antonio; Yoe, Hyun.; Jiménez Ramírez, Andres; Villarrubia, Gabriel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Ambient Intelligence (AmI) is a recent paradigm emerging from Artificial Intelligence, where computers are used as proactive tools assisting people with their day-to-day activities, making everyone's life more comfortable. Another main concern of AmI originates from the human computer interaction domain and focuses on offering ways to interact with systems in a more natural way by means user friendly interfaces. This field is evolving quickly as can be witnessed by the emerging natural language and gesture based types of interaction. The inclusion of computational power and communication technologies in everyday objects is growing and their embedding into our environments should be as invisible as possible. In order for AmI to be successful, human interaction with computing power and embedded systems in the surroundings should be smooth and happen without people actually noticing it. The only awareness people should have arises from AmI: more safety, comfort and wellbeing, emerging in a natural and inherent way. ISAmI is the International Symposium on Ambient Intelligence and aiming to bring together researchers from various disciplines that constitute the scientific field of Ambient Intelligence to present and discuss the latest results, new ideas, projects and lessons learned, namely in terms of software and applications, and aims to bring together researchers from various disciplines that are interested in all aspects of this area. .
A Benchmark Dataset for Human Activity Recognition and Ambient Assisted Living -- An Enhanced Real Space through Temporally Connecting Real and Virtual Scenes -- Detecting Social Interactions in Working Environments through Sensing Technologies -- Estimation of the Optimum Speed to Minimize the Driver Stress Based on the Previous Behavior -- Modelling Algorithms for Hierarchical Activity Discovery -- Estimating the Physical Activity with Smartphones: Analysis of the Device Position and Comparison with GT3X+ Actigraph -- An Application for Mobile Devices Focused on Clinical Decision Support: Diabetes Mellitus Case -- Customized Normalization Method to enhance the Clustering process of Consumption Profiles -- Dynamic Traffic Light Control System Based on Process Synchronization among Connected Vehicles -- Developing an Individualized Survival Prediction Model for Colon Cancer -- Providing Advanced Touristic Services by Means of Augmented Reality and Multimodal Dialog -- Creating Virtual Humans with Game Engines for Evaluate Ambient Assisted Living Scenarios -- Metabolic.Care: A Novel Solution Based on a Thermography for Detection of Diabetic Foot -- Identification of Activities of Daily Living Using Sensors Available in Off-the-shelf Mobile Devices: Research and Hypothesis -- Vox4Health: Preliminary Results of a Pilot Study for the Evaluation of a Mobile Voice Screening Application -- Assessing Interpersonal Trust in an Ambient Intelligence Negotiation System -- A Persuasive Cognitive Assistant System -- Preliminary Study of Classifier Fusion based Indoor Positioning Method -- Providing Wellness Services using Real Time Analytics -- Smart Cities Simulation Environment for Intelligent Algorithms Evaluation -- Hash-chain Based Authentication for IoT Devices and REST Web-Services -- Smart Computer-Assisted Cognitive Rehabilitation for the Ageing Population -- EEG Mapping for Arousal Level Quantification Using Dynamic Quadratic Entropy -- ARISTARKO: A Software Framework for Physiological Data Acquisition -- Vowel Recognition from RGB-D Facial Information.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence